Handover Management In Mobile Satellite Systems - Foo, Yee Loo (2003)
Two handover management strategies have been proposed to efficiently manage the channel resource of a cell in a mobile satellite system (MSS) and to improve its service quality by reducing the handover failure rate and drop call rate caused by insufficient number of communication channels.